Effectiveness Of Quality Bird Manure And Rice Straw Mulch On The Growth And Production Of Glutinous Corn Plants - Rosmaria Girsang; Yudi Siswanto; Ariani Syahfitri Harahap; Bayu Mahendra; Zamriyetti Zamriyetti (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
The study aims to determine the effectiveness of the application of quail manure and rice straw mulch on glutinous corn (Zea mays var. ceratina) growth and production and the interaction between the effectiveness of quail manure and rice straw mulch. This study used a factorial randomized block design (RBD) consisting of 2 factors with 16 combinations and 32 treatment plots. The first factor was applying quail manure (L) which consisted of 4 levels, 0 kg/plot, 0.85 kg/plot, 1.70 kg/plot, and 2.55 kg/plot. The second factor was the provision of rice straw mulch (Z) which consisted of 4 levels, 0 kg/plot, 1 kg/plot, 2 kg/plot, and 3 kg/plot. Parameters observed were plant height (cm), total leaf (strands), cobs weight per sample (g), cobs weight per plot (g), cob length (cm), and the number of rows (rows). The results showed that the application of quail manure and rice straw mulch affected the parameters of plant height (cm), total leaf (strands), cob weight per sample (g), cob weight per plot (g), cob length (cm) and the number of rows (lines). The interaction of giving quail manure and rice straw mulch did not affect the parameters of plant height (cm), total leaf (strands), cob weight per sample (g), cob weight per plot (g), cob length (cm) and the number of lines (row). The best treatment was found in quail manure and rice straw mulch, 2.55 kg/plot and 3 kg/plot.